2006
DOI: 10.1002/cncr.21895
|View full text |Cite
|
Sign up to set email alerts
|

Cancer‐specific survival and predictors of prostate‐specific antigen recurrence and survival in patients with seminal vesicle invasion after radical prostatectomy

Abstract: BACKGROUNDThe objectives of the current study were to determine the long‐term biochemical recurrence (BCR) and cancer‐specific survival (CSS) rates for men with seminal vesicle invasion (SVI) and to identify risk factors for freedom from BCR and CSS in patients who received treatment in the prostate‐specific antigen era and who had SVI identified at the time of radical prostatectomy (RP).METHODSProspective clinical, pathologic, and outcome data were collected for 5377 men who underwent RP between June 1983 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
41
4
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 22 publications
4
41
4
4
Order By: Relevance
“…Secin et al reported the probabilities of 10-year BCRFS in pT3bN1 and pT3bN0 patients to be 10% and 36%, respectively. 6 In the current study, the difference between 5-year BCRFS rates for lymph node metastasis and no lymph node metastasis was significant (0% and 18.2%, respectively, P < 0.001).…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…Secin et al reported the probabilities of 10-year BCRFS in pT3bN1 and pT3bN0 patients to be 10% and 36%, respectively. 6 In the current study, the difference between 5-year BCRFS rates for lymph node metastasis and no lymph node metastasis was significant (0% and 18.2%, respectively, P < 0.001).…”
Section: Discussionmentioning
confidence: 43%
“…Secin et al reported that a positive surgical margin was not an independent predictor of BCRFS in patients with SVI after radical prostatectomy, regardless of lymph node status. 6 In the current study, positive surgical margin was an independent predictor of BCRFS only in men with pT3bN0 tumors (HR 2.29, 95% CI 1.12-4.71, P = 0.024).…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…While the rate of SVI (pT3bN0) has more than halved from 7.%7 to 3.6%, SVI remains a strong predictor of biochemical recurrence and cancer specific mortality. 7,16 …”
Section: Discussionmentioning
confidence: 99%
“…7 A second analysis of 220 men similarly demonstrated a high rate of recurrence (54%) and no benefit to adjuvant or salvage therapy. 3 Using a larger, comprehensive database from our institution, we investigated outcomes in men with pT3b disease treated predominantly without ART in the contemporary era.…”
mentioning
confidence: 99%